Hybrid Energy Management of Solid Oxide Fuel Cell/Lithium Battery System - Dong Li; Xiaobo Zhong; Yuanwu Xu; Chongyang Wei; Song Zhao; Jianhua Jiang; Zhonghua Deng; Xiaowei Fu; Xi Li (CSEE Journal of Power and Energy Systems)
The research of the fuel cell and lithium battery hybrid system has attracted more and more researchers because of its advantages of low emission. However, the lower efficiency of energy management has been a critical factor that obstructs the commercialization of the hybrid system. In this study, based on finite element ideas, a solid oxide full cell node model is developed to accurately estimate the operating status of the fuel cell. As for the lithium battery, previous energy management studies generally only focused on the state of charge, however, the state of health is also a key parameter for lithium batteries. In this paper, considering the strong coupling between variables, we use a particle filter algorithm to jointly estimate the state of charge and state of health. To reasonably distribute and manage the energy in the hybrid system, a T-S fuzzy controller for the hybrid system is designed by controlling the state variables in the SOFC model and the state of lithium battery. Finally, our algorithm is verified by using the DSPACE simulation platform. The results show that the hybrid system with an energy management strategy not only meets the real-time sharply changing demands, but also ensures the hybrid system is working efficiently and safely.